Recurrent Brown Tumors as a Presenting Complaint of Primary Hyperparathyroidism: A Case Report - Muhammad Saad; Muhammad Rayan Syed; Ifrah Hamza; F. N. U. Dureshum; Khizer Masroor Anns; Hamza Aslam; Aleeza Syed; Faheemullah Khan; Ijaz Faraz (Clinical Case Reports)
ABSTRACT Brown tumor is a rare complication of hyperparathyroidism caused by bony remodeling. These tumors usually affect long bones, pelvis, and ribs, although every bone of the body can be involved. We report a case of a 36‐year‐old female who presented with complaints of swellings on the right mandible and left maxillary region. She had a history of a similar swelling on the right side of the maxilla that was excised surgically. This time, her incisional biopsy and lab work confirmed the diagnosis of brown tumors secondary to hyperparathyroidism. Parathyroidectomy was done for parathyroid adenoma, and the postoperative period was uneventful. Although brown tumor is rarely seen in clinical practice nowadays due to early detection of hyperparathyroidism, it is still an important differential diagnosis of bony tumors and oral masses.